Comparison of first dorsal metacarpal artery flap done by consultants and residents and guidelines for improving outcome for beginners - Hussain, Akram; Saleem, Abid; Yasir, Mir; Wani, Adil Hafeez; Mohsin, Mir; Farooq, Umer (International Journal of Research in Medical Sciences, 2016)
Background: Thumb alone constitutes about 40% of hand function and trauma to distal part of thumb will thus affect the overall hand function. The goals of correction of traumatic deformities of distal thumb are to maintain adequate length and sensation along with giving a supple and stable soft tissue cover. Among other options, first dorsal metacarpal artery (FDMA) flap raised from the dorsum of the proximal part of index finger is a simple and widely used flap. Methods: We compared the results of FDMA flap done by residents (M.Ch trainees) and consultants in our institute. Residents operated upon a total of 12 patients and consultants operated upon 16 patients. Results: Among 12 patients operated by residents 3 flaps were lost and 2 flaps had marginal necrosis whereas among the patients operated by consultants 1 flap was lost and 1 had partial necrosis in distal part of the flap. Conclusions: Although there was no statistical difference between the operating time taken by trainees and consultant specialists but the complication rate is higher among the residents. Sticking with the basics of plastic surgery, FDMA flap is an excellent technique for thumb reconstruction and results are excellent as and when more experience is gained.